2015
DOI: 10.1007/s10753-015-0296-9
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Quercetin on Acute Lung Injury and Biomarkers of Inflammation and Oxidative Stress in the Rat Model of Sepsis

Abstract: Experimental studies indicate that sepsis causes remote organ injury although the molecular mechanism has not been clearly defined. In this report, the role of oxidative damage, and inflammation on lung injury, following sepsis model by cecal ligation and puncture, and the effects of quercetin, antioxidant, and anti-inflammatory flavonoid, in the lung tissue were investigated. In the present study, we found that administration of single-dose quercetin before cecal ligation and puncture procedure, while markedl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 29 publications
1
45
0
Order By: Relevance
“…MPO is a marker of oxidative stress except for neutrophil infiltration. In addition, therapeutic strategies to protect the mitochondria by decreasing oxidative stress during sepsis have been recognized [4850]. Our study showed that the levels of ROS detected by DHE fluorescence and MPO by immunofluorescence were markedly increased after the CLP treatment and decreased in the KO-CLP mice compared with the WT-CLP mice in the lung and liver.…”
Section: Discussionmentioning
confidence: 60%
“…MPO is a marker of oxidative stress except for neutrophil infiltration. In addition, therapeutic strategies to protect the mitochondria by decreasing oxidative stress during sepsis have been recognized [4850]. Our study showed that the levels of ROS detected by DHE fluorescence and MPO by immunofluorescence were markedly increased after the CLP treatment and decreased in the KO-CLP mice compared with the WT-CLP mice in the lung and liver.…”
Section: Discussionmentioning
confidence: 60%
“…Finally, we found that CFH independently increases lung F 2 -isoprostanes and isofurans, markers of increased oxidant stress, in this polymicrobial sepsis model. Increased oxidant stress in the lung during sepsis has been well described in cecal ligation and puncture models [40][41][42][43] but none of these studies examined CFH as a potential mediator of oxidant injury. The CLP model of sepsis also has elevated circulating CFH, raising the possibility that some of its oxidant effects could be due to CFH [44].…”
Section: Discussionmentioning
confidence: 99%
“…We have already demonstrated that ExoS can cause an in ammatory response and improve clearance in the lungs in vitro and vivo [26]. It is also well known that quercetin is a useful substance for various diseases [27][28][29]. However, it is not known whether quercetin prevents disease by inhibiting the expression of ExoS due to infection of the host via T3SS of P. aeruginosa.…”
Section: Discussionmentioning
confidence: 99%